Security enhancements to vehicle communication networks - Choo, Caleb Zhe Wei (2018)
In recent years, more emphasis has been placed on the research of Vehicle Ad-hoc Network (VANET) to provide communication channels for various applications. These applications include safety, driving assistance, traffic efficiency as well as infotainment. There is an Enhanced Secure and Privacy VANET-based navigation scheme (EVSPN) currently proposed, this scheme offers signature and verification on Public Key Infrastructure (PKI) and prevents man-in-the-middle attacks. However, the EVSPN comes at a cost too. It also generates significant financial costs and significant authentication delays for both vehicles as well as Roadside Units (RSU). In this report, I have proposed an Advanced Secure VANET-based Navigation Scheme (ASVN). The ASVN is much lower in terms of cost and has a lower authentication delay as compared to EVSPN. The ASVN introduces a 2-step approach. Firstly, a vehicle initiates the navigation service by using a RSU that is within its vicinity to request a shared seed. Secondly, it generates a one-way hash chain of keys to allow more in-dept communication with other RSUs in the VANETs. This will result in the calculation of the best route possible. As a result, the pseudo identity of the vehicle and the hash chain of keys are sent to the RSUs that are along the vehicle’s navigation route. By using BAN Logic, we can prove that the ASVN scheme can provide better guarantee of the integrity of messages as well as mutual authentication.